Initiatives proposed in conjunction with the preparation of the 11th Malaysia plan: strengthening entrepreneurial training / Rozita @ Uji Mohammed - Uji Mohammed, Rozita @ (Universiti Teknologi MARA Sabah, Kota Kinabalu, 2016)
This paper was initially prepared in the form of a strategy paper. It has been forwarded to the state government through the Sabah State Economic Planning Unit (UPEN) in conjunction with the preparation of the 11th Malaysia Plan (11MP) (2016-2020) at the state level. In March 2014, UPEN had initiated five Technical Working Groups (known as TWG) with different tasks assigned to each group. TWG5, which was led by UiTM Sabah branch and accompanied by 10 other agencies, aimed for the construction of viable ideas in strengthening the entrepreneurial training of local micro, small and medium enterprises (SMEs). Entrepreneurial training has become one of the main agendas of the SME Master Plan (2012 - 2020) launched by Prime Minister Datuk Seri Najib Razak on 12 July 2012. This strategic plan defined the direction of SMEs in all sectors towards achieving Malaysia's goal of becoming a high income nation by the year 2020. This study also reflects the National Development Policy (NDP) in the formation of the Bumiputera Commercial and Industrial Community (BCIC). Hence, this study highlights issues with regards to entrepreneurial training, and proposes comprehensive initiatives to support local entrepreneurs by interconnecting the relevant ministries, agencies and relevant parties. This study also prepares a strategy for SMEs to cope with the knowledge-based economy (k-economy).